Development of Embrio Tourism Village Into Developing Tourism Village : Case Study: Telaga Biru Tourism Village Bangkalan Madura - Muntaha, Baitul Ma’mur; Prakoso, Aditha Agung; Isdarmanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Telaga Biru Tourism Village is a destination that offers the concept of rural life as its attraction located in Tanjung Bumi Village, Bangkalan, Madura. As a Tourism Village categorized as an Embrio Tourism Village, there are many successes that have been achieved by this Village such as being able to turn waste dumps into tourist attractions, tourism activities carried out in the Village can become the original income of the village that is able to prosper the local community, and so on. However, in its application, there are still many shortcomings that need to be addressed by the management of Telaga Biru Village. This study aims to find out the appropriate strategy in making Telaga Biru Village, which is now an Embrio Tourism Village, become a Developing Tourism Village. The type of research used is qualitative research. The results of this study show that there is a need for the fulfillment of tourism village components such as building accommodation for overnight tourists and improving tourism village management such as the need for human resources who have competence in the field of tourism so that tourists can travel more comfortably.